The acquired pco gene cluster in Salmonella enterica mediates resistance to copper - Hikal, Ahmed F.; Hasan, Sameer; Gudeta, Dereje; Zhao, Shaohua; Foley, Steven; Khan, Ashraf A. (Frontiers in Microbiology, 2024)
The pervasive environmental metal contamination has led to selection of heavy-metal resistance genes in bacteria. The pco and sil clusters are located on a mobile genetic element and linked to heavy-metal resistance. These clusters have been found in Salmonella enterica serovars isolated from human clinical cases and foods of animal origin. This may be due to the use of heavy metals, such as copper, in animal feed for their antimicrobial and growth promotion properties. The sil cluster can be found alone or in combination with pco cluster, either in the chromosome or on a plasmid. Previous reports have indicated that sil, but not pco, cluster contributes to copper resistance in S. enterica Typhimurium. However, the role of the pco cluster on the physiology of non-typhoidal S. enterica remains poorly understood. To understand the function of the pco gene cluster, a deletion mutant of pcoABCD genes was constructed using allelic exchange mutagenesis. Deletion of pcoABCD genes inhibited growth of S. enterica in high-copper medium, but only under anaerobic environment. Complementation of the mutant reversed the growth phenotype. The survival of S. enterica in RAW264.7 macrophages was not affected by the loss of pcoABCD genes. This study indicates that the acquired pco cluster is crucial for copper detoxification in S. enterica, but it is not essential for intracellular replication within macrophages.